Digital Technologies: Sustainable Innovations for Improving Teaching and Learning (Springer International Publishing, 2018)
The aim of this volume entitled Digital Technologies: Sustainable Innovations for improving Teaching and Learning is to contribute in the global discussion on digital technologies as the means to foster sustainable educational innovations for improving the teaching, learning and assessment from K-12 to Higher Education. The book consists of four parts and showcases how emerging educational technologies and innovative practices have been used to address core global educational challenges; spanning from rethinking and transforming learning environments across educational contexts to effectively cultivating students' competences for the digital smart society of the future. The book comprises Part I: Transforming the Learning Environment; Part II: Enriching student learning experiences; Part III: Measuring and Assessing Teaching and Learning with Educational Data Analytics; Part IV: Cultivating student competences for the digital Smart society. It targets researchers and research students, educational professional practitioners (including teachers, educators and education leaders) as well as education policy makers, who are interested in keeping up-to-date on the global development in this field.